(untitled) (Discourse of Law and Administration, 2023)
In the construction of modern states, a particularly important role was played by the combination of supreme, central government, with the dominance of the power of society in the regions. The emergence of the modern state poses many difficulties for legal historians, especially concerning time, but also space. In the area of the Holy Roman Empire, the multiplicity of states and their internal differentiation strengthened the construction of this type of state, an example of which is Silesia, as well as Bavaria, Hesse, or Bohemia. The paper focuses mainly on the administrative factor, but also on the underlying social factor. The construction of a modern administration, sometimes absolutist, encountering local resistance, is one of the most important factors in the emergence of modern states, not only in the 15th century, as the article puts it, but also from the 13th century onwards, as Anglo-Saxon historians would rather boldly have it.